A study of bus services in Karachi, Pakistan - Nauman, Syed Ali; Yordphol Tanaboriboon; Mori, Hiroshi; Fukuda, Atsushi; Asian Development Bank (Japan Scholarship Program) (Bangkok : Asian Institute of Technology, 1991)
Presently there are four types of bus services in Karachi operated by both public and private operators. Minibuses and private ordinary buses are operated by the private franchise while Karachi Transport Corporation ( KTC) is responsible for public ordinary and express bus services. These four types of bus systems were examined in this research study. Each bus route of the four bus types namely W 11, Orangi Express , 6 and 1 D were selected to represent the minibus, public express bus, private ordinary bus and public ordinary bus, respectively. Operational analysis revealed that there were inconsistencies in headways and for all selected bus routes, bus bunching and unaccepted large gaps between buses were noticed. However, private bus services had shorter mean headways and more number of buses running on the selected routes when compared to KTC selected routes. It was ·found out that in most of the selected routes, travel time were shorter in morning peak when compared to the evening peak on most of the sections. However, large variations and inconsistencies were found for travel time for different time periods. Similarly layover time were found to have inconsistencies between origin and destination terminals. Large discrepancies on the layover time were noticed for all four selected bus routes in particular the minibuses. The dominance of male over female respondents was clearly evident in all the four bus services because of the cultural traditions. Most of the users use the particular bus service daily or on every working day. More than half to three fourth of the users traveled between 10-45 minutes range. Overcrowding was reported as the major problem by users in case of minibus and ordinary bus services while more number of buses and of latest models were demanded by express bus service users. Most of the users expressed their waiting time as " unsuitable " . Seat availability on all bus services was reported to be seldom. This overcrowding was reflected by the users traveling by sitting on the roof of minibuses and standing on door with body outside the bus. The largest category of users rated all bus services as " fair " except for KTC ordinary bus service which was rated as "poor". A large number of respondents of all bus services reported the present fare to be expensive. Ordinary bus passengers were ready to switch over to express bus service provided fare can be reduced while minibus users preferred to remain with the minibus. An increase in the bus fleet size with bus priority lanes are recommended. Merger of individualized operators into a single company or organization could result in better service. A time schedule and its adherence need priority attention. Safety of the users should be given due consideration.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Transportation -- Pakistan -- Karachi; Traffic engineering -- Pakistan -- Karachi; Bus lines -- Pakistan -- Karachi